Isolation, characterization and analysis of multi-drug resistant Acinetobacter baumannii isolated from hospital adjacent lake soil in Dhaka city - Hossain, MD. Walid; Dey, Rimon Chandra (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2023.